Hazard Ratio Analysis of Laparoscopic Radical Hysterectomy for IA1 With LVSI-IIA2 Cervical Cancer: Identifying the Possible Contraindications of Laparoscopic Surgery for Cervical Cancer - Li, Pengfei; Liu, Ping; Yang, Ying; Wang, Lu; Liu, Jiaqi; Bin, Xiaonong; Lang, Jinghe; Chen, Chunlin (Frontiers in Oncology, 2020)
OBJECTIVES: To compare the 5-year disease-free survival (DFS) and overall survival (OS) of laparoscopic radical hysterectomy (LRH) and abdominal radical hysterectomy (ARH) for IA1with LVSI-IIA2 cervical cancer and to analyse the Cox proportional hazard ratio of LRH among the total study population and different subgroups. METHODS: This was a multicentre retrospective cohort study. The oncological outcomes of LRH (n= 4236) and ARH (n= 9177) were compared. The hazard ratios (HR) and 95% confidence intervals for the effect of LRH on 5-year OS and DFS were estimated by Cox proportional hazards models. RESULTS: Overall, there was no difference in DFS between LRH and ARH in the unadjusted analysis (HR 1.11, 95% CI: 0.99-1.25, p=0.075). The risk-adjusted analysis revealed that LRH was independently associated with inferior DFS (HR 1.25, 95% CI: 1.11-1.40, p<0.001). There was no difference in OS between the two groups in the unadjusted analysis (HR 1.00, 95% CI: 0.85-1.17, p=0.997) or risk-adjusted analysis (HR 1.15, 95% CI: 0.98-1.35, p=0.091). For patients with FIGO stage IB1 and tumor size＜2cm, LRH was not associated with lower DFS or OS (p=0.637; p=0.107) in risk-adjusted analysis. For patients with FIGO stage IB1 and tumor size ≥2cm, LRH was associated with lower 5-year DFS (HR 1.42, 95% CI 1.19-1.69, p＜0.001) in risk-adjusted analysis, but it was not associated with lower 5-year OS ( p=0.107) . For patients with FIGO stage IIA1 and tumor size＜2cm, LRH was not associated with lower 5-year DFS or OS (p=0.954; p=0.873) in risk-adjusted analysis. For patients with FIGO stage IIA1 and tumor size ≥2cm, LRH was associated with lower DFS (HR 1.48, 95% CI 1.16-1.90, p=0.002) and 5-year OS (HR 1.69, 95% CI 1.22-2.33, p=0.002) in risk-adjusted analysis. CONCLUSION: The 5-year DFS of LRH was worse than that of ARH for FIGO stage IA1 with LVSI-IIA2. LRH is not an appropriate option for FIGO stage IB1 or IIA1 and tumor size≥2cm compared with ARH, .